Africa RISING-Farmer Perception of Forage Chopping Machines in Babati District - International Livestock Research Institute (International Livestock Research Institute, 2015)
A total of 20 farmers were selected by farmer groups from 7 AR action sites in Babati district. Farmer?s selection was based on experience, activeness in forage processing and willing to be a farmer trainer. The selected farmers were trained on the benefits and importance of forage processing and how to process forages and poultry feed using livestock feed processing machines. After the training, a farmer perception check list was administered to each farmer trained to assess their perception of the processing machine. To learn more about this dataset, please visit the ILRI Datasets Portal http://data.ilri.org/portal/dataset/africa-rising-farmer-perception-of-forage-chopping-machines-in-babati-district